Effect of Food to Microbe Ratio Variation on Anaerobic Co-Digestion Of Petrochemical Wastewater with Manure - Siddique, Md. Nurul Islam; Mimi Sakinah, A. M.; Zularisam, A. W. (Elsevier Ltd, 2016)
This work was performed to investigate the influence of the food-to-microbe (F/M) proportion on anaerobic co-digestion of petrochemical wastewater (PWW) and activated manure (AM) in a continuous stirred tank reactor (CSTR). As the F/M proportion varied from 0.25 to 2.0 and organic loadings from 6.31 to 32 (g VS/L), the cumulative biogas generation and the cumulative methane generation was enhanced from 571 to 855 mL/g VS and 425 to 499 mL/g VS at mesophilic (37 ºC) state and 620–909 mL/g VS and 519–553 mL/g VS at thermophilic (55 ºC) state in 145 days of co-digestion period. The VS and TS removal increased from 55% to 77% and 43% to 53% under mesophilic conditions and from 62% to 79% and 34% to 46% under thermophilic conditions when the F/M ratio increased from 0.5 to 2.0, respectively